Evaluating Virtual Human Role-Players for the Practice and Development of Leadership Skills - Suárez, Gonzalo; Jung, Sungchul; Lindeman, Robert W. (Frontiers in Virtual Reality, 2021)
This article reports on a study to evaluate the effectiveness of virtual human (VH) role-players as leadership training tools within two computer-generated environments, virtual reality (VR) and mixed reality (MR), compared to a traditional training method, real human (RH) role-players in a real-world (RW) environment. We developed an experimental training platform to assess the three conditions: RH role-players in RW (RH-RW), VH role-players in VR (VH-VR), and VH role-players in MR (VH-MR), during two practice-type opportunities, namely pre-session and post-session. We conducted a user study where 30 participants played the role of leaders in interacting with either RHs or VHs before and after receiving a leadership training session. We then investigated (1) if VH role-players were as effective as RH role-players during pre- and post-sessions, and (2) the impact that the human-type (RH, VH) in conjunction with the environment-type (RW, VR, MR) had on the outcomes. We also collected user reactions and learning data from the overall training experience. The results showed a regular increase in performance from pre- to post-sessions in all three conditions. However, we did not find a significant difference between VHs and RHs. Interestingly, the VH-MR condition had a more significant influence on performance and task engagement compared to the VH-VR and RH-RW conditions. Based on our findings, we conclude that VH role-players can be as effective as RH role-players to support the practice of leadership skills, where VH-MR could be the best method due to its effectiveness.